Identifying and Ranking Security Indicators in Online Social Networks with an MADM Technique - Hamed Fathi; Alireza Amini (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aims to identify and rank security indicators in online social networks. Social networks include Facebook, Twitter, Telegram, WhatsApp, YouTube, and Instagram.Methodology: The information technology units of Melli Bank have been studied, and 30 people have been considered research experts. For this purpose, seven important indicators were identified, and the TOPSIS technique was used to prioritize them. Then, the relationship between the identified indicators and online social network security was investigated using the Spearman correlation test. For this purpose, a questionnaire with 24 items was distributed, and 262 samples were collected and analyzed.Findings: The results show that security indicators in online social networks in order of priority are implementing authentication and licensing mechanisms, using up-to-date software and avoiding suspicious programs, restricting personal information dissemination, monitoring to prevent unauthorized processing of information, compliance with standards the country's IT infrastructure, and the installing an intruder detection system. Also, based on the results of the Spearman correlation test, all factors have had a positive and significant effect on social network security.Originality/Value: In this study, we concluded that there is a significant relationship between the influential factors and the security of social networks on the line defined for these networks. The development of information and communication technology infrastructures and the increase in users using virtual social networks justifies the need to create and develop a mechanism for establishing security in these communication networks.